2006
DOI: 10.1016/j.compedu.2005.11.007
|View full text |Cite
|
Sign up to set email alerts
|

How can exploratory learning with games and simulations within the curriculum be most effectively evaluated?

Abstract: (2006

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
293
0
29

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 557 publications
(323 citation statements)
references
References 16 publications
1
293
0
29
Order By: Relevance
“…As explained in Section 3.1, the experiential learning theory of Kolb (1984), and Gardner's theory of multiple intelligences (1983) were used in the design of our game. Other works have pointed out the importance of considering national curricula in the development of educational computer games (de Freitas & Oliver, 2006;Lai-Chong Law et al, 2008). We have taken the Spanish national curricula into account to design our game.…”
Section: Discussionmentioning
confidence: 99%
“…As explained in Section 3.1, the experiential learning theory of Kolb (1984), and Gardner's theory of multiple intelligences (1983) were used in the design of our game. Other works have pointed out the importance of considering national curricula in the development of educational computer games (de Freitas & Oliver, 2006;Lai-Chong Law et al, 2008). We have taken the Spanish national curricula into account to design our game.…”
Section: Discussionmentioning
confidence: 99%
“…As a result it was a relatively straightforward, narrative based activity and was limited in the extent to which it could reflect the dynamic and complex nature of work-based practice compared with both more complex game based activities (Gee, 2003;Rouse, 2005;de Fritas, 2006;) and face to face teaching. It is also important (de Freitas and Oliver, 2006) but more difficult to take account of individual learning characteristics in a flexible way in an online learning activity. Despite this, both the online activity and the face to face teaching were designed to take account of good learning principles, such as providing challenge, the opportunity to learn through experimentation and experience, rather than through the rote learning of facts, and surprising feedback, i.e.…”
Section: Participant Evaluations Of the Learning Activitymentioning
confidence: 99%
“…CAST, working as a scaffolding resource, provides a more able partner in Luckin's terms, and provided for improvisation, discovery and testing (Schön, 1983(Schön, , 1987. Previous research found that learners need the opportunity to ruminate, evaluate, reformulate, compare, and integrate the material to be learned during the CAST to create reflections on the their experiences (Dalgarno & Lee, 2010;de Freitas & Oliver, 2006;Holzinger, Kickmeier-Rust, Wassertheurer, & Hessinger, 2009;Rieber et al, 2004). Overall, the computer simulation has to provide responses to actions taken by the user to accomplish reflection-in-action while providing feedback based on the training provided to the user.…”
Section: The Computer Simulation Resource (Tool)mentioning
confidence: 99%